Invensi Pertunjukan Gerbang Etam Orchestra dalam Erau International Folk Arts Festival - Kapri, Riana; Sushartami, Wiwik; Irawati, Eli (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2020)
Gerbang Etam Orchestra is a musical group that is always present at the Erau International Folk Arts Festival. Gerbang Etam Orchestra has a characteristic performance by combining Kutai Kartanegara ethnic music with a mass format. The purpose of this research is to identify the form of the Gerbang Etam Orchestra performance to review the use of the term “orchestra” whether it is in accordance with the rules of the music. This study used a qualitative method with an ethnomusicological approach to see the phenomenon of music which is influenced by hybridity and produces invention. This study uses Eric Hobsbawm's theory, the invention of tradition. The data analyzed were the results of observations, interviews, audio and video recordings. Furthermore, the data were analyzed using qualitative data analysis techniques by means of data reduction, data presentation, drawing conclusions and data verification. The results showed that the use of the term orchestra at the Gerbang Etam Orchestra produced a form of performance that had similar characteristics to orchestras in general. Even though it uses the term Western music, Gerbang Etam Orchestra still emphasizes the distinctive characteristics of Kutai Kartanegara ethnic music which is owned as a regional identity. This is manifested in the form of performances presented by the Gerbang Etam Orchestra.Keywords: Gerbang Etam Orchestra, Invention, Ethnic Music, Orchestra